Between Conflict and Kinship: Understanding the Social Identity of Bangsamoro Orphans in Maguindanao and North Cotabato Province - Abadi, Mansurni; Wulandari, Wulandari (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2024)
Abstract The persistent conflict in the Bangsamoro area, located in the southern Philippines, has markedly affected numerous individuals, particularly the offspring of deceased mujahideen fighters. This study delves into the configuration of social identity among orphans of Bangsamoro mujahideen, exploring their navigation of belonging within a community characterized by enduring conflict and radicalization. Rooted in historical grievances, socio-political marginalization, and the pursuit of self-determination, the Bangsamoro conflict has spawned radical groups that further complicate the societal dynamics within the region. Employing a qualitative methodology, this research integrates in-depth interviews, participant observations, and analysis of local narratives to comprehend the construction of social identities among these orphans. The study investigates the impacts of family, community, and radical ideologies on their identity formation and how they reconcile their orphanhood with the necessity for belonging in a fractured society. The findings expose the identity struggles faced by orphans of Bangsamoro mujahideen, as they navigate between victimhood and the glorification of their parents' legacies. Radicalization and the pervasive conflict environment significantly influence their perceptions of self and others, often leading to the embracement of ideologies that resonate with their experiences of loss and marginalization. The study concludes that the social identity of these orphans is a multifaceted interplay of personal experiences, community influences, and broader socio-political contexts. It underscores the critical need for targeted interventions to address the psychological and social needs of these children, thereby averting further radicalization and fostering a more inclusive sense of belonging in the Bangsamoro region.